PENDIDIKAN BERKUALITAS (Upaya Menuju Perwujudan Civil Society) - Azzuhri, Muhandis (IAIN Pekalongan, 2009)
A qualified education can provide a right view about the process of changing views of society by setting up human resources that are righteous in God the Almighty, possesing virtuous noble character, having good personality, productive, physically and mentally healthy, independent, advanced, powerful, smart, knowledgeable, creative, skilled, disciplined, professional, responsible, socially minded, and be oriented to the future. In achieving this goal, education must be tailored to the needs of civil society that is humane, universal, democratic, in accordance with local and national cultures, capable of balancing between IMTAQ and IPTEQ as well as nondichotomous accordingly be accomodative and applicative to all.